2012
DOI: 10.1002/nvsm.1432
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the decision‐making processes for arts sponsorship

Abstract: Corporate support is a significant revenue stream for non-profit organisations, yet little is known of the actual decision paths companies take when making these decisions and what characterises these paths. This study seeks to develop a greater understanding of decision processes for companies considering sponsorship of the arts. A multiple-case study approach was taken, with participants from arts organisations and paired sponsoring companies, resulting in the finding of three decision paths: one characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Sponsorship is a form of communication that is used extensively by corporations to promote their brands or products through cultural events. A handful of studies have examined the relationship of sponsorship with the effectiveness of the message (Carillat, Colbert, & Feigné, ; Carillat, D'Astous, & Colbert, ; Colbert, D'Astous, & Parmentier, ) or with the decision‐making process (Daellenbach, ). Other components of private funding for the arts have also been examined—for instance, the brand personality of the organization and its influence on giving (Stebbins & Hartman, ).…”
Section: Arts Marketing Managementmentioning
confidence: 99%
“…Sponsorship is a form of communication that is used extensively by corporations to promote their brands or products through cultural events. A handful of studies have examined the relationship of sponsorship with the effectiveness of the message (Carillat, Colbert, & Feigné, ; Carillat, D'Astous, & Colbert, ; Colbert, D'Astous, & Parmentier, ) or with the decision‐making process (Daellenbach, ). Other components of private funding for the arts have also been examined—for instance, the brand personality of the organization and its influence on giving (Stebbins & Hartman, ).…”
Section: Arts Marketing Managementmentioning
confidence: 99%
“…While past studies have examined the extent to which senior vs middle-level managers are involved in these decisions (eg. Madden, 2006;Brammer et al, 2006;Brennan et al, 2012;Daellenbach, 2012), the perspective revealed here is that both levels of manager may be involved, each with their own sensemaking strategy. CE's bring their values and backgrounds to contribute to the sensemaking, not unlike processes suggested in strategic decision making (Hambrick and Mason, 1984).…”
Section: Domain Of Inquirymentioning
confidence: 96%
“…Authors note difficulties in measuring the success of sponsorship (be it arts, sports or social) (Thjømøe et al, 2002, Dolphin, 2003, Cornwell et al, 2005, and find that consumers and other stakeholder groups may be sceptical of corporate associations with non-profits (Alcañiz et al, 2010;Sen and Bhattacharya, 2001;Seitanidi and Ryan, 2007, p. 259). Consistent with this, decision makers considering arts sponsorship may also view these initiatives with some uncertainty (Daellenbach, 2012;Daellenbach et al, 2013). However, the specific strategies which decision-makers go through, to make sense of these situations has not been investigated, leading us to examine the literature on sensemaking.…”
Section: Theoretical Background 21 Arts Sponsorship and Decision Makingmentioning
confidence: 99%
See 1 more Smart Citation
“…So, sponsorship activities are other investigation area for art marketing research (e.g. Colbert et al, 2005, Daellenbach et al, 2006Daellenbach, 2012). Waters and Fenely (2013) emphasized that new media tools are an important tool for promotion of non-profit organizations such as art organizations.…”
Section: Marketing Activities For Artistic Productsmentioning
confidence: 99%